Fraternity, conflict and political realism. Keys to thinking about integration from Latin America - Del Percio, Enrique (Teoría y Praxis, 2012)
Fraticide has existed since the origin of the city: Cain and Abel, Romulus and Remus and many other examples. Because of that, departing from fraternity as a cornerstone of political theory is feasible to develop a framework of analysis and proposals that take the conflict as inherent to the human condition. If the own vice of freedom is selfishness and the one for equality is envy, the one for fraternity is jealousy brothers feel. Just as selfishness makes reference to the existence of self, and envy to the existence of the other, jealousy refers to a third party. This reference to a third party sees politics as an experimental search for a necessarily provisional justice. TEORÍA Y PRAXIS Year 10, No.21, June-December 2012, pp.3-35